Upaya Guru PAI untuk Meningkatkan Literasi Keamanan Digital di SMPN 2 Jati Agung - Beti Susilawati; Juni Hartiwi; Zahra Rahmatika; Ais Istiana (Departement of Mathematics Education, 2024)
Digital security literacy is a concept and effort to give protection to the assets and digital information. The higher the information technology development, the more the use of tool and digital technology. Since the number of data theft, online fraud, and the hacking of data system increase day by day, the all users need to have competency in digital security. The role of Islamic education teachers as educators are not only to share knowledge, but they also have to be able to keep the environment around and the ability for teachers as skying on cyber world. Teachers should be literated with digital security as long they do the learning process. Based on the problems above, the writers aimed to know the efforts of teachers in increasing the competency of the teachers in using the digital security. This research used qualitative method, and it used observation, speech training, and simulation/direct practice in collecting the data. The result of research indicated that the Islamic education teachers are able to employ the digital information (E-resources) via internet access by using google application to seek the legal learning sources. The teachers are also able to use google form, google document, whatsapp and facebook well and safely.